ANALISIS MANAJEMEN RANTAI PASOK BAWANG GORENG PALU - Nuriyanti Nuriyanti; Saharia Kassa; Arifuddin Lamusa Lamusa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimed to determine the mechanism of supply chain management of Palu fried shallots. The research was carried out in severallocations i.e. Soulowe village of Sigi Biromaru subdistrict, Nunu and Masomba villages of East Palu sub district, and Wombo Kalonggo village of Tavaeli sub district, during July 2016. Respondents were 22 peopleconsisted of 14 shallot suppliers, twowholesalers, oneretailer, threeindustries, and three customers. Data was analyzedusing a descriptive analysis. The members of networking of the fried Palu shallot are farmers – collector trader – industry – retailer/market – consumer with each one has its own task.  There were four channels of the supply mechanisms: the product channel flows from the farmers to the end consumers; the information channel flows in two directions from the farmers and the market agencies such as the collector traders and the retailers to the consumers; the fund channel flows from the consumers to the retailer, the industry, and the collector trader/market; and the activity channel flow from the farmers up to the retailers/market.  The business partnership as the supply chain management strategy of the fried Palu shallot had been well organized. Keywords:Palu fried shallot, and Supply chain management.